Crossover from incoherent to coherent phonon scattering in epitaxial oxide superlattices - Ravichandran, Jayakanth; Yadav, Ajay K.; Cheaito, Ramez; Rossen, Pim B.; Soukiassian, Arsen; Suresha, S. J.; Duda, John C.; Foley, Brian M.; Lee, Che-Hui; Zhu, Ye; Lichtenberger, Arthur W.; Moore, Joel E.; et al. (Nature materials, 2014)
Understanding the thermal transport properties of superlattice structures is relevant to a number of possible practical applications. Now, the scattering of phonons in oxide superlattices is shown to undergo a crossover from an incoherent to a coherent regime, which in turn strongly alters their thermal behaviour. Elementary particles such as electrons 1 , 2 or photons 3 , 4 are frequent subjects of wave-nature-driven investigations, unlike collective excitations such as phonons. The demonstration of wave–particle crossover, in terms of macroscopic properties, is crucial to the understanding and application of the wave behaviour of matter. We present an unambiguous demonstration of the theoretically predicted crossover from diffuse (particle-like) to specular (wave-like) phonon scattering in epitaxial oxide superlattices, manifested by a minimum in lattice thermal conductivity as a function of interface density. We do so by synthesizing superlattices of electrically insulating perovskite oxides and systematically varying the interface density, with unit-cell precision, using two different epitaxial-growth techniques. These observations open up opportunities for studies on the wave nature of phonons, particularly phonon interference effects, using oxide superlattices as model systems, with extensive applications in thermoelectrics and thermal management.